2000
DOI: 10.1007/s002130000393
|View full text |Cite
|
Sign up to set email alerts
|

Socio-psychological stress-induced antinociception in diabetic mice

Abstract: These results indicate that emotional stress can readily induce antinociception in diabetic mice. Furthermore, this enhanced emotional stress-induced antinociception might be attributable to an increase in the production and/or release of endogenous ligands for benzodiazepine receptors, such as diazepam binding inhibitor, which act as inverse benzodiazepine receptor agonists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…Furthermore, socio-psychological stress-induced antinociception in diabetic mice was significantly reduced by treatment with diazepam (24). We also demonstrated that treatment with flumazenil significantly antagonized the socio-psychological stress-induced antinociception in diabetic mice (24). On the other hand, >-CCM significantly and dose-dependently enhanced the socio-psychological stress-induced antinociception in non-diabetic, but not in diabetic mice (24).…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…Furthermore, socio-psychological stress-induced antinociception in diabetic mice was significantly reduced by treatment with diazepam (24). We also demonstrated that treatment with flumazenil significantly antagonized the socio-psychological stress-induced antinociception in diabetic mice (24). On the other hand, >-CCM significantly and dose-dependently enhanced the socio-psychological stress-induced antinociception in non-diabetic, but not in diabetic mice (24).…”
Section: Discussionmentioning
confidence: 53%
“…We also demonstrated that treatment with flumazenil significantly antagonized the socio-psychological stress-induced antinociception in diabetic mice (24). On the other hand, >-CCM significantly and dose-dependently enhanced the socio-psychological stress-induced antinociception in non-diabetic, but not in diabetic mice (24). Based on these results, we suggested that some endogenous substance(s) that act(s) as an inverse benzodiazepine receptor agonist may also be involved in the enhancement of socio-psychological stress-induced antinociception in diabetic mice (24).…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations